PKM Kelompok Pendamping Diabetes Self Management Education (KP-DSME) Bebasis Keluarga di Kelurahan Penggaron Lor Kecamatan Genuk Kota Semarang - Dyah Wiji Puspita Sari; Rita Kartika Sari; Muh Abdurrouf (Journal of Dedicators Community, 2018)
The service was done at Penggaron Lor Districk, especially in RW 03 & 04, there are many people with diabetes who lack the knowledge and skills in caring for family members suffering from Diabetes Mellitus at home. Community service activities in the form of Family-Based Self Management Education Support Group (KP-DSME Keluarga) is one of the solutions to deal with this problem. The method used to carry out this Community service activities program are socialization, improvement of competence, implementation of activities, monitoring and evaluation. The resulting target and output is the implementation of science and technology on the self-care of diabetitian patients to health cadres in providing assistance to families who have diabetitian at home effectively based on recent literatures. The number of cadres involved in this PKM are 14 health cadres from PKK RW 3 and 4 PKK. The conclusion in this PKM activity is increasing the readiness of family members to perform self-care on family members who suffer from DM and increasing diabetee self care behavior.